Miss Jane : a novel - Watson, Brad (W. W. Norton & Company, 2016)
"Astonishing prose brings to life a forgotten woman and a lost world in a strange and bittersweet Southern pastoral. Since his award-winning debut collection of stories, Last Days of the Dog- Men, Brad Watson has been expanding the literary traditions of the South, in work as melancholy, witty, strange, and lovely as any in America. Inspired by the true story of his own great-aunt, he explores the life of Miss Jane Chisolm, born in rural, early-twentieth-century Mississippi with a genital birth defect that would stand in the way of the central "uses" for a woman in that time and place--namely, sex and marriage. From the country doctor who adopts Jane to the hard tactile labor of farm life, from the highly erotic world of nature around her to the boy who loved but was forced to leave her, the world of Miss Jane Chisolm is anything but barren. Free to satisfy only herself, she mesmerizes those around her, exerting an unearthly fascination that lives beyond her still"--Provided by publisher.